Temporal Lobe Epilepsy: Electroclinical Features - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
Results of video-EEG, PET, MRI, and pathological findings in 14 children aged 16 months to 12 years who were seizure-free after temporal lobectomy are reported in a multicenter, international study at Cleveland, Singapore, Naples, and Helsinki.